Development and signal transduction in Dictyostelium - Kim, H; Kim, Hyun Ji (Williams) (1999)
Dictyostelium, is a simple eukaryote that multiplies as separate amoebae. However when nutrients are no longer available it embarks on a developmental programme in which the amoebae collect together by chemotaxis and the resulting aggregates eventually transform into fruiting bodies consisting of a cluster of spores held up on a cellular stalk. The entire process of development normally takes about 24 hours. However there are mutants, termed rapidly developing mutants (rde) which complete development in about two-thirds of this time. RdeA null mutants have been reported to have elevated levels of cyclic AMP that may lead to increased activity of the enzyme, cAMP dependent protein kinase (PKA). I started my work by measuring total cAMP levels in an rdeA mutant along with an aca-/rdeA- double mutant that is expected to have very low level of cAMP due to the absence of the adenylyl cyclase, AC A. Two Dictyostelium adenylyl cyclases were known at the beginning of my work; one is AC A the aggregative enzyme, and the other ACG, expressed only during spore germination. Contrary to expectation, I detected cAMP in aca-/rdeA cells. This raised the question of which enzyme was responsible for producing this cAMP. In collaboration with Dr.Pauline Schaap, I discovered a novel adenylyl cyclase that I initially detected in rdeA and regA mutants but not in wild-type cells. The product of the rdeA gene, RDEA was thought to be an H2-module histidine phosphotrasferase of the kind acting in multi-step phosphorelays. Similarly REGA was believed to be a response regulator associated with a cAMP-phosphodiesterase. It had been proposed that RDEA phosphorylates REGA in a multi-step phosphorelay and it had been shown that it is the phosphorylated form of REGA that is active as a cAMP-PDE. I therefore thought that cAMP produced by the novel AC could be protected in rdeA mutants by the absence of the REGA cAMP-PDE activity and this idea was supported by my finding that the enzyme activity could also be detected in wild-type (aca-) cells when REGA-PDE was inhibited by IBMX. In order to investigate further the proposed phosphorelay model, I tested for possible interaction between RDEA and REGA using the yeast two-hybrid system and also measured intracellular cAMP-phosphodiesterase activity in rdeA and regA mutants. I found that the interaction between RDEA and REGA appeared to be too transient to be detected in the two-hybrid system. In addition rdeA and regA mutants seemed to have levels of intracellular cAMP-phosphodiesterase activity similar to wild type. However REGA-PDE activity measured specifically by immuno-precipitation was completely absent in the regA mutant. It therefore appeared that there is another intracellular cAMP-phosphodiesterase, in addition to the REGA PDE, in Dictyostelium and that the latter cannot be easily detected in total cell lysates. One possible explanation is that the novel adenylyl cyclase exists together with REGA in a complex (that may also include PKA) and that REGA PDE preferentially destroys the cAMP made by the novel adenylyl cyclase. I conclude that rdeA and regA mutants may develop rapidly due to high PKA activity induced by the accumulation of cAMP made by the novel AC when the REGA cAMP-PDE activity is absent.